Correction: Maladaptive perfectionism can explain the inverse relationship between dispositional mindfulness and procrastination. - Gozde Ibili; Jeremy John Tree; Yılmaz Orhun Gurluk (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0318845.].